Psychometric Properties of the Resistance to Framing Scale: Evidence from Indonesia - Hidayat, Rahmat; Pertiwi, Ajeng Putri (JP3I (Jurnal Pengukuran Psikologi dan Pendidikan Indonesia), 2025)
This paper reports the validation of the Indonesian version of the resistance to framing effects scale, which is part of the Adult Decision-Making Competence Index (A-DMC). Framing refers to an individual’s tendency to be influenced by how information is structured. The resistance to framing effects scale is a measurement tool designed to assess an individual’s susceptibility to framing. This scale comprises two dimensions: attribute framing and risky-choice framing. A total of 217 participants (60 men and 157 women) completed the 14-item scale. Item Response Theory and the Multidimensional Graded Response Model (MGRM) were used to evaluate the psychometric properties of the scale. The MGRM analysis results indicated that the data fit the model, as evidenced by global fit statistics. Additionally, all items showed a good fit with the MGRM model. The reliability of this scale was 0.697 for the attribute dimension and 0.722 for the risky-choice dimension. However, we found that one item had low discrimination (ATT5 with a = 0.638), while the remining 13 items had optimal discrimination. Based on these results, we conclude that the 14-item Indonesian version of the resistance to framing effects scale is a reliable measurement tool that can be used for future research in behavioral economics or economic psychology in Indonesia. There are limitations of this study: the relatively small sample size and the lack of convergent validity testing with other instruments. However, the strong psychometric properties observed in this study suggest that this instrument is suitable for use in future research and may also be applied for practical measurement purposes.